Early reconstruction of the leaking ileal pouch‐anal anastomosis: a novel solution to an old problem. (May 2015) - Gardenbroek, T. J.; Musters, G. D.; Buskens, C. J.; Ponsioen, C. Y.; D'Haens, G. R. A. M.; Dijkgraaf, M. G. W.; Tanis, P. J.; Bemelman, W. A.
Abstract: Aim: The study aimed to determine the effectiveness and direct medical costs of early surgical closure of the anastomotic defect after a short course of Endo‐sponge® therapy of the presacral cavity, compared with conventional treatment in patients with anastomotic leakage after ileal pouch‐anal anastomosis (IPAA). Method: Patients with anastomotic leakage after IPAA undergoing early surgical closure of the anastomotic defect after a short Endo‐sponge® treatment were prospectively followed and compared with a consecutive cohort of patients with an anastomotic leak treated by creation of a loop ileostomy and occasional drainage of the presacral cavity. Results: A total of 15 patients were treated with early surgical closure and 29 were treated conventionally. In the early surgical closure group, the Endo‐sponge® treatment was continued for a median of 12 days [interquartile range (IQR) 7–15 days] with a median of 3 (IQR 2–4) Endo‐sponge® changes. Secondary anastomotic healing was achieved in all patients ( n  = 15) in the early surgical closure group compared with 52% ( n  = 16) in the conventional treatment group ( P  = 0.003). Closure of the anastomotic defect was achieved after a median of 48 (25–103) days in the early surgical closure group compared with 70 (IQR 49–175) days in the conventional treatment group ( P  = 0.013). A functional pouch was seen in 93% and 86% of the patients in each group. There was no significant difference in direct medical cost. Conclusion: Early surgical closure after a short period of Endo‐sponge® treatment is highly effective in treating anastomotic leakage after IPAA without increasing cost.